Makna Pesan Moral Film Perjalanan Pertama (Model Roland Barthes) - Ali Waskito; Utami, Sinta Dwi (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The film "Perjalanan Pertama" by Arief Malinmudo is important to observe because it is not just an ordinary journey but teaches the process of maturity through a physical journey between a grandfather and his grandson. This study aims to determine the moral message contained in the film. This study implies a qualitative method, Roland Barthes' semiotics, because this method is relevant to analyze the moral message hidden behind the symbols and signs in the film. The data is collected by observing film clips that have signs and symbols that represent the moral message. The primary data in this study is the film "Perjalanan Pertama", while secondary data was obtained through social media, the internet, and journals relevant to this study. The data analysis technique was taken through three levels: the denotative level, the connotative level, and the myth level. The results of this study are: (1) The importance of honesty and accepting reality in the past; (2) Intergenerational relationships, namely setting aside ego and learning from each other's lives; (3) Sincerity; (4) Finding identity through a long journey.